T cell antigen receptor signaling and immunological synapse stability require myosin IIA. - Ilani, T; Vasiliver-Shamis, G; Vardhana, S; Bretscher, A; Dustin, M (2009)
Immunological synapses are initiated by signaling in discrete T cell antigen receptor microclusters and are important for the differentiation and effector functions of T cells. Synapse formation involves the orchestrated movement of microclusters toward the center of the contact area with the antigen-presenting cell. Microcluster movement is associated with centripetal actin flow, but the function of motor proteins is unknown. Here we show that myosin IIA was necessary for complete assembly and movement of T cell antigen receptor microclusters. In the absence of myosin IIA or its ATPase activity, T cell signaling was interrupted 'downstream' of the kinase Lck and the synapse was destabilized. Thus, T cell antigen receptor signaling and the subsequent formation of immunological synapses are active processes dependent on myosin IIA.